2011
DOI: 10.1002/cmdc.201100100
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Existence of a Specific G Protein‐Coupled Receptor Activated by Guanosine

Abstract: Guanosine, released extracellularly from neurons and glial cells, plays important roles in the central nervous system, including neuroprotection. The innovative DELFIA Eu-GTP binding assay was optimized for characterization of the putative guanosine receptor binding site at rat brain membranes by using a series of novel and known guanosine derivatives. These nucleosides were prepared by modifying the purine and sugar moieties of guanosine at the 6- and 5'-positions, respectively. Results of these experiments p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…Indeed, a G-protein-coupled site seems to be important for the neuroprotective effects of this nucleoside, namely, during the guanosine-induced stimulation of glutamate uptake and the release of trophic factors by astrocytes [39,82,86]. In support of this hypothesis, binding sites for guanosine, distinct from the well-characterized P1 and P2 receptors, were found in rat brain membranes [87][88][89]. In addition, experimental evidence suggests that this binding site has an important role in signal transduction mediated by this nucleoside [39,82,86].…”
Section: Metabolism and Intracellular Signaling Pathways Triggered Bysupporting
confidence: 57%
“…Indeed, a G-protein-coupled site seems to be important for the neuroprotective effects of this nucleoside, namely, during the guanosine-induced stimulation of glutamate uptake and the release of trophic factors by astrocytes [39,82,86]. In support of this hypothesis, binding sites for guanosine, distinct from the well-characterized P1 and P2 receptors, were found in rat brain membranes [87][88][89]. In addition, experimental evidence suggests that this binding site has an important role in signal transduction mediated by this nucleoside [39,82,86].…”
Section: Metabolism and Intracellular Signaling Pathways Triggered Bysupporting
confidence: 57%
“…GUO prevents the decrease in cell viability, by increasing glutamate uptake and glutamine synthetase activity, decreasing glutamate release, ROS production and inflammatory mediators expression, including reduction of iNOS expression [14,15,33,40]. The exact interaction site of GUO in cellular membranes is still unknown, although it has been suggested [41,42]. GUO effects over adenosinergic system are controversial [43], but we have shown that neuroprotective effects of GUO depend on adenosine receptors modulation [33] and on activation of a calcium-dependent potassium channel [14].…”
Section: Discussionmentioning
confidence: 99%
“…1 and Table 1). In addition, a great deal of evidence suggests that both Urd [83,84] and Guo [50,51] may bind to their selective receptors, most likely the G-proteincoupled receptors UrdR and GuoR, in the CNS (Fig. 1). …”
Section: The Nucleoside System In the Brainmentioning
confidence: 99%
“…Guo may bind to its putative (uncloned) G-protein-coupled receptors in the brain [50,51]. Guanosine levels increased after PTZ-induced seizures [372], and Guo exerts a protective effect on quinolinic acid (QA)-induced seizures [60-62, 368, 373-377] (Table 4) and -dendrotoxin-induced seizures [371] likely by stimulation of astrocytic glutamate uptake [89,373,377,378].…”
Section: Non-adenosine Nucleosides: Uridine Guanosine and Inosinementioning
confidence: 99%
See 1 more Smart Citation